Introduction to microcredit industry in Malaysia / Zuraidah Mohamed Isa ... [et al.] - Mohamed Isa, Zuraidah; Ibrahim, Dahlia; Ali, Norhidayah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
In Malaysia, the provision of microcredit is nothing new. Malaysia's microcredit institutions have different types of lending systems, specifically the group-based lending system and the individual lending system. Malaysia's microfinance institutions also have a standardised lending contract apart from offering limited microfinance products. In this regard, Malaysia's microfinance institutions only offer microcredit loan with no microsavings or microinsurances. The limitation of the financial services is due to the restriction by the Malaysia Banking and Financial Act 1989 that states "No person shall carry on banking services, including receiving deposits on current account, deposit account, saving account or no other similar account, without a licence as a bank or financial institutions".